Validity of the global physical activity questionnaire (GPAQ) in Bangladesh - Shirin Jahan Mumu; Liaquat Ali; Anthony Barnett; Dafna Merom (BMC, 2017)
Abstract Background Feasible and cost-effective as well as population specific instruments for monitoring physical activity (PA) levels are needed for the management and prevention of non-communicable diseases. The WHO-endorsed Global Physical Activity Questionnaire (GPAQ) has been widely used in developing countries, but the evidence base for its validity, particularly for rural populations, is still limited. The aim of the study was to validate GPAQ among rural and urban residents in Bangladesh. Methods A total of 162 healthy participants of both genders aged 18-60 years were recruited from Satia village (n = 97) and Dhaka City (n = 65). Participants were invited to take part in the study and were asked to wear an accelerometer (GT3X) for 7 days, after which they were invited to answer the GPAQ in a face to face interview. Results Valid accelerometer data (i.e., ≥10 h of wear times over ≥3 days) were received from 155 participants (rural = 94, urban = 61). The mean age was 35 (SD = ±9) years, 55% were females and 19% of the participants had no schooling, which was higher in the rural area (21% vs 17%). The mean ± SD steps/day was 9998 ± 3936 (8658 ± 2788 and 12,063 ± 4534 for rural and urban respectively, p = 0.0001) and the mean ± SD daily moderate-to-vigorous physical activity (MVPA) was 58 ± 30 min (51 ± 26 for rural and 69 ± 34 for the urban, p = 0.001) for accelerometer. In case of GPAQ, rural residents reported significantly higher moderate work related PA (MET-minutes/week: 600 vs. 360 p = 0.02). Spearman correlation coefficients between GPAQ total MVPA MET-min/day and accelerometer MVPA min/day, counts per minute (CPM) or steps counts/day were acceptable for urban residents (rho: 0.46, 0.55 and 0.63, respectively; p < 0.01) but poor for rural residents. The overall correlation between the GPAQ and accelerometer for sitting was low (rho: 0.23; p < 0.001). GPAQ-Accelerometer correlation for MVPA was higher for females (rho: 0.42), ≤35 age group (rho: 0.31) and those with higher education attainment (rho: 0.48). The Bland-Altman plots illustrated bias towards over estimation of GPAQ MVPA with increased activity levels for urban and rural residents. Conclusion GPAQ is an acceptable measure for physical activity surveillance in Bangladesh particularly for urban residents, women and people with high education. Given waist worn accelerometers do not capture the typical PA in rural context, further study using a physical activity diary and a combination of multiple sensors (e.g., wrist, ankle and waist worn accelerometers) to capture all movement is warranted among rural population with purposive sampling of all education levels.